2018
DOI: 10.1038/s41374-018-0027-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide CRISPR screen reveals SGOL1 as a druggable target of sorafenib-treated hepatocellular carcinoma

Abstract: The genome-wide clustered regularly interspaced short palindromic repeats (CRISPR) screen is a powerful tool used to identify therapeutic targets that can be harnessed for cancer treatment. This study aimed to assess the efficacy of genome-wide CRISPR screening to identify druggable genes associated with sorafenib-treated hepatocellular carcinoma (HCC). A genome-scale CRISPR knockout (GeCKO v2) library containing 123,411 single guide RNAs (sgRNAs) was used to identify loss-of-function mutations conferring sora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…A genome wide CRISPR screening study revealed that loss of SGOL1, a protein involved in mitosis, is the main cause of resistance to sorafenib in HuH7 and SMMC-7721 HCC cells. Further in vivo studies showed decreased sorafenib cytotoxicity and increased tumor size supporting contribution of SGOL1 to sorafenib resistance [46]. These findings suggest that SGOL1 might be a suitable therapeutic target for HCC patients and individuals with SGOL1 overexpression might be appropriate candidates to be treated with sorafenib.…”
Section: Liver Cancermentioning
confidence: 67%
“…A genome wide CRISPR screening study revealed that loss of SGOL1, a protein involved in mitosis, is the main cause of resistance to sorafenib in HuH7 and SMMC-7721 HCC cells. Further in vivo studies showed decreased sorafenib cytotoxicity and increased tumor size supporting contribution of SGOL1 to sorafenib resistance [46]. These findings suggest that SGOL1 might be a suitable therapeutic target for HCC patients and individuals with SGOL1 overexpression might be appropriate candidates to be treated with sorafenib.…”
Section: Liver Cancermentioning
confidence: 67%
“…sgRNAs in the cells affect their competence for viability during the proliferation. The enrichment or depletion of these sgRNAs thereupon reveals the genes responsible for the cognate phenotype (82)(83)(84)(85)(86)(87)(88).…”
Section: Crispr/cas Genome-wide Knockout Screeningmentioning
confidence: 99%
“…The discovery of the host factors and receptor for Norovirus, the leading cause of gastroenteritis, was the result of CRISPR screens using LVs for the delivery of the sgRNA library [ 155 ]. Similarly, Sun et al identified new drug targets conferring sorafenib resistance in the treatment of hepatocellular carcinoma [ 156 ].…”
Section: Delivery Strategies For Therapeutic Applicationsmentioning
confidence: 99%